THE ANALYSIS OF SEMANTICS METAPHOR IN THE SONG LYRICS “THE NIGHT IS STILL YOUNG” BY NICKI MINAJ (Argopuro: Jurnal Ilmu Bahasa, 2025)
This research discusses the use of semantic metaphors in the lyrics of the song “The Night Is Still Young” by Nicki Minaj. This research was conducted using a qualitative descriptive method and Lakoff and Johnson's conceptual metaphor theory to identify and analyze various metaphorical expressions that build deep meanings in the song lyrics. The analysis shows that metaphors such as “the night is still young,” “get twisted,” and “aim for the stars” not only embellish the lyrics, but also represent the themes of freedom, youth, optimism, and self-empowerment. Through metaphors of time, parties, and aspirations, the song invites listeners to enjoy life, take advantage of opportunities, and not be afraid to dream big. In addition, these metaphors also strengthen the emotional connection between the singer and the listener, and reflect cultural values about youth and freedom. This research shows that the use of metaphors in popular music can be an effective means of conveying universal messages that are relevant to everyday life experiences. The findings are expected to contribute to linguistic, literary and cultural studies, particularly in understanding the role of language in shaping meaning and experience through song lyrics.Keywords: Semantic, Metaphor, Lyrics, Song, Youth